Conditional Cancer Survival of the Corpus Uterine in the USA. Issue 4 (October 2016) - Merrill, Ray M.; Frutos, Aaron M.
Purpose: To identify relative survival probabilities for corpus uterine cancer patients accounting for time already survived, as well as age, race, ethnicity, marital status, tumor stage, and tumor grade at diagnosis. Methods: Analyses are based on 78, 147 women diagnosed with corpus uterine cancer during 2000-2008 and followed through 2013, using data from the National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) program. Results: Age, race, marital status, tumor stage, and tumor grade, but not ethnicity, significantly impacted relative cancer survival rates of the corpus uterine. Improvement in 5-year relative survival, when conditioned on 1-5 years already survived, occurs in each stage category, more so in later staged cases. The effect of age, race, marital status, and tumor grade on 5-year relative survival, after conditioning on years (1 -2 -3 -4 -5 ) already survived, varied by stage at diagnosis. For example, poorer prognosis with older age was only observed for regional and distant staged cases, but being married had a greater beneficial impact in regional and distant staged cases. The difference in 5-year relative survival rates diminished for age, race, marital status, tumor stage and grade when conditioned on years (1 -2 -3 -4 -5 ) already survived. The greatest improvement in 5-year conditional relative survival was in patients 70 years or older, Blacks, singles, later staged tumors, and higher grade tumors. Conclusions: Reporting cancer survival estimates according to time already survived and demographic subgroups provide health-care providers and patients with more instructive prognostic information.